Consistent responses with guselkumab treatment in Asian and non‐Asian patients with psoriasis: An analysis from VOYAGE 1 and VOYAGE 2. Issue 12 (20th October 2019) - Reich, Kristian; Song, Michael; Li, Shu; Jiang, Jingzhi; Youn, Sang Woong; Tsai, Tsen‐Fang; Choe, Yong Beom; Huang, Yu‐Huei; Gordon, Kenneth B.
Abstract: Guselkumab, an interleukin‐23 blocker, was superior to placebo and adalimumab and well‐tolerated in phase 3 psoriasis studies (VOYAGE 1 and VOYAGE 2). This analysis evaluated the consistency of response in the Asian subpopulation in VOYAGE 1 and VOYAGE 2. Study designs were identical through week 24; patients were randomized to guselkumab, placebo, or adalimumab. Investigator's Global Assessment (IGA), Psoriasis Area and Severity Index (PASI), safety, and pharmacokinetic and immunogenicity data from VOYAGE 1 and VOYAGE 2 were pooled and compared by race (Asian, n  = 199; non‐Asian, n  = 1630). At week 16, treatment differences between guselkumab and placebo were 78.2 (95% confidence interval [CI], 66.9–89.6) and 76.4 (95% CI, 72.7–80.2) percentage points for IGA 0/1 (score of 0 or 1) and 70.1 (95% CI, 60.0–80.1) and 68.5 (95% CI, 64.9–72.2) percentage points for PASI 90 (≥90% improvement) in the Asian and non‐Asian populations, respectively. Treatment differences between guselkumab and adalimumab were 31.1 (95% CI, 17.7–44.6) and 16.1 (95% CI, 11.2–21.0) percentage points for IGA 0/1 and 24.9 (95% CI, 9.4–40.5) and 23.2 (95% CI, 17.7–28.6) percentage points for PASI 90 in the Asian and non‐Asian populations, respectively. Similar results were observed at week 24. Safety was generally similar between populations and among treatment groups. Median serum guselkumab concentrations over time were comparable between the populations. Comparable responses between the Asian and non‐Asian populations in this analysis suggest that the overall efficacy, safety, and the resulting benefit/risk analyses from VOYAGE 1 and VOYAGE 2 are applicable to Asian populations.